Like art Glenn O'Brien on advertising - O'Brien, Glenn 1947-2017 (Karma, 2017)
"Like Art" was the title of my Artforum column that ran from 1985 to 1990, but it was also my philosophy of advertising. Advertising was like art, and more and more art was like advertising. Ideally the only difference would be the logo. Advertising could take up the former causes of art--philosophy, beauty, mystery, empire. We were clearly living in a time of extremist hypocrisy where various forms of creative work descried one another. Price-gouging painters looked down onlowly craftsmen and entertainment journeymen. Millionaire rock stars adopted a quasi-communist stance, emphasizing the anti-commercia aspect of their work. From back cover
2000, special edition of 100 hardcover copies
Keywords: Geschichte 1985-1990; Werbung; Commercial art; Aufsatzsammlung